Multimedia applications development using Indeo video and DVI technology - Bunzel, Mark J. (Intel/McGraw-Hill series, 1994)
Examines the process behind the construction of a multimedia production, including implementations with ActionMedia II, Windows and OS/2. The book offers guidance on issues such as selecting the appropriate DVI hardware and software and setting up a multimedia workstation.